2024
DOI: 10.4081/monaldi.2024.2745
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of chronic obstructive pulmonary disease in Morocco: a cost of illness study

Soumaya Benmaamar,
Btissame Es-sabbahi,
Mohammed Taghyioullah Haiba
et al.

Abstract: Chronic obstructive pulmonary disease (COPD) carries an important economic burden worldwide. However, the cost of this disease in Morocco is not well explored. This study aimed to estimate the economic cost associated with COPD in Morocco and identify its determinants. A cost of illness, prevalence-based study using a bottom-up approach method, including COPD patients, was carried out in 2021-2022. The cost was estimated from a societal perspective, and the time horizon was 1 year. Data collection was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…23–25 COPD is a major public health problem in Morocco. 15 , 26 , 27 Our study revealed a prevalence of 6.7%. This value is lower than that reported by a previous national study, which reported a prevalence of 12.6%.…”
Section: Discussionmentioning
confidence: 44%
“…23–25 COPD is a major public health problem in Morocco. 15 , 26 , 27 Our study revealed a prevalence of 6.7%. This value is lower than that reported by a previous national study, which reported a prevalence of 12.6%.…”
Section: Discussionmentioning
confidence: 44%